Diabetes in Cystic Fibrosis: Multicenter Screening Results Based on Current Guidelines - Scheuing, Nicole (Public Library of Science, 2013)
BACKGROUND: Published estimates on age-dependent frequency of diabetes in cystic fibrosis (CF) vary widely, and are based mostly on older data. However, CF treatment and prevention of comorbidities changed over recent years. In many studies, definition of cystic fibrosis-related diabetes (CFRD) is not in line with current guideline recommendations. Therefore, we evaluated age-dependent occurrence of glucose abnormalities and associated risk factors in CF patients who participated in a multicenter screening program using oral glucose tolerance tests (OGTT). METHODS: Between 2001 and 2010, 43 specialized CF centers from Germany and Austria serially performed 5,179 standardized OGTTs in 1,658 clinically stable, non-pregnant CF patients with no prior steroid medication or lung transplantation. Age-dependent occurrence of impaired fasting glucose (IFG), impaired glucose tolerance (IGT), IFG+IGT, one (DGT) or two consecutive (CFRD) diabetic OGTTs was analyzed, using Kaplan Meier curves. Cox proportional-hazards models were created to elucidate the influence of sex or underweight. RESULTS: At baseline/last OGTT, median age was 15.9 years/18.2 years and 30.6%/31.8% of patients were underweight. 25% of patients showed IFG at age 14.3 years; IGT at age 16.3 years; IFG+IGT combined at age 17.7 years. DGT was observed in 25% of patients at age 22.6 years; CFRD at age 34.5 years. Females had a 3.54 [95% CI 1.23–10.18] times higher risk for CFRD; risk for DGT was 2.21 [1.22–3.98] times higher. Underweight was a risk factor for IGT (HR [95% CI]: 1.38 [1.11–1.71]) and IFG+IGT (1.43 [1.11–1.83]), and in males also for DGT (1.49 [1.09–2.04]). CONCLUSIONS/SIGNIFICANCE: If confirmation of diabetes by a second test is required, as recommended in current guidelines, age at CFRD diagnosis was higher compared to most previous studies. However, known risk factors for glucose abnormalities in CF were confirmed. Confirmation of diabetic OGT by a repeat test is important for a consistent diagnosis of CFRD.